2021
DOI: 10.1038/s41598-021-92112-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics study of plasma from patients suggest that ALS and PLS are part of a continuum of motor neuron disorders

Abstract: Motor neuron disorders (MND) include a group of pathologies that affect upper and/or lower motor neurons. Among them, amyotrophic lateral sclerosis (ALS) is characterized by progressive muscle weakness, with fatal outcomes only in a few years after diagnosis. On the other hand, primary lateral sclerosis (PLS), a more benign form of MND that only affects upper motor neurons, results in life-long progressive motor dysfunction. Although the outcomes are quite different, ALS and PLS present with similar symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 69 publications
1
46
1
Order By: Relevance
“…Modification of glycerophospholipid metabolism by ACY-738 is accompanied by the amelioration of motor performances, the integrity of neuromuscular junctions, and significantly increased the survival of FUS mice. Moreover, a recent study showed that ALS patients are characterized by dysregulated glycerophospholipid blood levels at an early stage of the disease and that specific glycerophospholipids species correlate with disease progression [ 24 , 76 ]. Therefore, these particular lipid alterations could serve as effective biomarkers, prognosis markers, and potent indicators for the effectiveness of new HDAC inhibitors, adding a stepping stone for the rapid development of innovative treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Modification of glycerophospholipid metabolism by ACY-738 is accompanied by the amelioration of motor performances, the integrity of neuromuscular junctions, and significantly increased the survival of FUS mice. Moreover, a recent study showed that ALS patients are characterized by dysregulated glycerophospholipid blood levels at an early stage of the disease and that specific glycerophospholipids species correlate with disease progression [ 24 , 76 ]. Therefore, these particular lipid alterations could serve as effective biomarkers, prognosis markers, and potent indicators for the effectiveness of new HDAC inhibitors, adding a stepping stone for the rapid development of innovative treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identification of a lipidomic signature may be relevant to detect potential diagnostic, prognostic, and predictive biomarkers in various diseases [33]. Moreover, the study of the concentrations of a subset of lipids in human disease can shed light into cellular processes and unravel alterations in one or more pathways [34]. Lipids can be studied by targeted or untargeted lipidomics, both using high resolution Mass Spectrometry (MS).…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of PC C36:4 have been observed in the cerebrospinal fluid (CSF) of ALS patients [ 9 ]. By contrast, decreased levels of total PCs have been reported in the plasma of ALS patients and have shown significant increases in follow-up samples of patients [ 21 ]. Our study further elucidated the reduced plasma levels in ALS patients of 31 specific PCs, 14 of which were significantly correlated with the ALSFRS-r scores.…”
Section: Discussionmentioning
confidence: 99%